Cirsium hupingshanicum (Asteraceae, Cardueae), a new species from Hunan, China - Jin, Zi-Chao; Chen, You-Sheng (Phytotaxa, 2022)
Cirsium hupingshanicum Z. C. Jin & Y. S. Chen, a new species of the Asteraceae from Hunan, China, is described and illustrated. This new species is similar to C. japonicum Fisch. ex DC. and C. racemiforme Ling et C. Shih. It differs from C. japonicum in its white corolla, plant ca. 120–180 cm high and basal leaf blade elliptic. It can readily be distinguished from the latter by its white corolla, long pedicel, basal leaves shape and morphology of capitula.